PENANDA HUBUNGAN GRAMATIKAL DAN LEKSIKAL DALAM BERITA KOMPAS EDISI BULAN APRIL 2022 - Fitria Indah Nugroho; Atiqa Sabardila (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2023)
The purpose of this article is to identify grammatical and lexical forms of cohesion in the discourse in the april 2022 issue of the kompas.com site's online news. This article uses a descriptive qualitative method with a text analysis type of research. Data collection techniques are carried out by recording words, phrases, clauses and sentences that have grammatical and lexical cohesion forms. Based on data analysis obtained in the form of grammatical cohesion and lexical cohesion, namely efficiency, substitution, demonstrative, comparative, ellipsis, and conjunction. while in lexical cohesion, namely repetition, synonymy, antonymy, collocation, and hyponymy. The total of the total data found amounted to 32. Grammatical cohesion data totaled 19 data, with details: persona reference 3 data, demonstrative 4 data, comparative 1 data, substitution 4 data, ellipsis 2 data, and conjunction 5 data. Meanwhile, the lexical cohesion data totaled 13 data with details: reps 4 data, synonymy 2 data, antonymy 3 data, collocation 1 data, and hyponymy 3 data.